Relationship between Family Support and Spirituality of HIV Patients in Tanjung Balai - Nunung Febriany Sitepu; Alexander; Muhammad Naufal Zain (Health and Technology Journal (HTechJ), 2023)
Family support is a form of interaction in which there is a relationship that gives and receives real help carried out by the family. This support can be in the form of attitudes, actions, and family acceptance of sick patients. In family support, spirituality is needed, which involves an individual's relationship with others and the world. Spirituality is also often associated with self-discovery and the meaning of life. This study aimed to look at the relationship between family support and spirituality in people with HIV / AIDS in the city of Tanjung Balai. This research method is an observational correlation, with a cross-sectional approach where researchers use questionnaires to 50 respondents who got HIV, using a total sampling technique. Inclusion criteria: 1) respondents who get HIV, 2) willing to be a respondent, 3) can communicate well, 4) willing to cooperate, 5) age 20-50 years. The measurement of spirituality used of spiritual well-being questionnaire (SWBQ) and family support measurement used to measure respondents. This study showed a relationship between family support and spirituality in people with HIV / AIDS (p < 0.05). Family support and spirituality can be a factor that can support people with HIV / AIDS to accept the process of self-acceptance.